The Relation between Symptoms of Computer Vision Syndrome and Visual Display Terminal Utilization - Rozanna Fithri Nadhiva; Mulyono Mulyono (Universitas Airlangga, 2020)
Introduction: The increased use of computers in the era of technological advances had an impact on the eye health called Computer Vision Syndrome (CVS), a compound eye problem caused by computer use. Almost every job could not be separated from the use of computers. Based on data from World Health Organization (WHO) in 2014, the incidence of asthenopia (eye fatigue) ranged from 40% to 90%. This research aimed to determine the relationship between symptoms of Computer Vision Syndrome and Visual Display Terminal utilization. Methods: This research was a quantitative with analytic survey method. Based on the data collection method, this research included as observational research type. This research was conducted with cross-sectional study design. Data collection was carried out with doctor's diagnosis guidelines, interviews, measurement using questionnaires, and observation. The population was 47 permanent workers and the sample taken was 42 respondents from the design division workers. The sampling technique used simple random sampling. The variables in this research were age, working period, distance to VDT, and general lighting intensity. Results: This research showed that the factors associated with symptoms of Computer Vision Syndrome were working period and eye distance to VDT. Conclusion: The longer the working period and the more distance between the eye and the VDT, the more symptoms of VDT would be.Keywords: computer use, symptoms of computer vision syndrome, visual display terminal